Serum Calcium and Its Association with Preeclampsia (Bangladesh Journal of Medical Science, 2021)
Background: The purpose of the study was to evaluate association of serum calcium concentration with preeclampsia.Method: This study was carried out in the Department of Obstetrics and Gynaecology of Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh from January 2016 to December 2016 including 120 antenatal patients in their second half of pregnancy. All the included patients were classified as 40 mild preeclampsia (Group A) 40 severe preeclampsia (Group B) and 40 normal pregnant women (Group C). Serum calcium was estimated in the Department of Biochemistry and correlated with preeclampsia.Result: In results the mean serum calcium concentration was found 8.2±0.2mg /dl in Group A, 7.6 ± 0.3 mg/dl in Group B and 9.0±0.5 mg/dl in Group C (p=0.001). Low serum calcium was found 53.7% and 12.5% in case and control respectively. The difference was statistically significant (p=